Strategic actions according to Jürgen Habermas – some critical remarks from the transcendental-pragmatic procedure viewpoint - Filipiak, Magdalena (Lingua Posnaniensis, 2017)
The purpose of this paper is to analyze the primacy of communicative rationality in relation to other forms of rationality and to determine the status of openly strategic actions in the concept of Jürgen Habermas. In the theory of communicative actions, Habermas focuses on actions secretively strategic, recognizing them as “parasitic” in relation to communicative actions and explains the prevalence of communicative actions on the grounds of the theory of speech acts, in particular the concept of illocutionary force, the category of “social binding force”, or practice in the lifeworld. By the same, Karl-Otto Apel challenges Habermas that he has skipped explicitly strategic class of actions, which entails the inadequacy of the justification for the status of communicative rationality. This raises a doubt – why should non-strategic actions take precedence over strategic ones? Karl-Otto Apel replies to this question with the help of transcendental-pragmatic procedure of an ultimate justification.